Unfabling the East : the enlightenment's encounter with Asia - Osterhammel, Jürgen (Princeton University Press, 2018)
During the long eighteenth century, Europe's travelers, scholars, and intellectuals looked to Asia in a spirit of puzzlement, irony, and openness. In this panoramic and colorful book, Jürgen Osterhammel tells the story of the European Enlightenment's nuanced encounter with the great civilizations of the East, from the Ottoman Empire and India to China and Japan.